Fenología y ecofisiología de Gliricidia sepium (Jacq. ) Steud, "Madero Negro" en Ciudad Colón, Costa Rica - Fournier O., Luis A.; Herrera de Fournier, María E. (Revista de Biología Tropical, 1986)
Leaf flushing, leaf fall, flowering and fruiting were observed during three years in a population of 20 trees of Gliricidia sepium growing in a coffee plantation in Ciudad Colón, Costa Rica (780.m.a.s.l.). These four phenological characteristics showed a strong periodicity during the year with little variations in the period of the study. Leaf fall occurs practically the year around, but it is more pronouced during dry season (December to March). Shoots grow constantly, but this process is more active during the wet season. A positive correlation was determined bewtween shoot growth and soil humidity, but in the case of leaf fall this correlation was negative. Flowering and fruiting occur during dry season (December-April) reaching a maximun on February. It is suggested that the phenology of this species is strongly correlated with soil humidity, but internal rhytms are al so considered important.